Fpgas-Based Edge Computing with Distributed Leader Election on Internet of Things - Toledo-De la Garza, K; Fernandez-Campusano, C (Institute of Electrical and Electronics Engineers Inc., 2023)
This paper presents a flexible architecture for the Internet of Things (IoT) with edge computing based on Field Programmable Gate Arrays (FPGAs) and distributed leader election (DLE). An enhanced DLE algorithm is introduced which implicitly monitors the communication nodes on the wireless sensor networks (WSNs) and chooses the appropriate leader to improve the reliability of the system. At the edge computing layer, devices rely on hardware description language to leverage the versatility and parallel processing capabilities of FPGAs. We also perform simulations and hardware implementation to evaluate the performance of specific tasks. Numerical results evidence the rise of the leader and how the data from network nodes are utilized to distinguish signals from noise successfully. © 2023 IEEE.